Pemikiran Filsafat John Calvin dan Relevansinya - John Christianto Simon (Jurnal Teologi (JUTEOLOG), 2021)
This paper departs from the problems encountered in the context of human suffering due to the Covid-19 pandemic regarding the ideal social human figure that is relevant at this time. This paper intends to explain the philosophical thoughts of a church reformer, John Calvin. The research method used in this paper is descriptive-interpretative in order to construct the thoughts of a character by looking at the relationships in the context of his life. The main question is how did Calvin's philosophical ideas emerge and are contextualized today? The method of discussion is first to explain Calvin and the context of his life, secondly Calvin's philosophy about humans, thirdly Calvin's philosophy and its actualization in church and state (public education), fourth, Calvin's philosophy and its actualization in the context of the covid-19 pandemic and lastly some conclusions. The result of this research is that Calvin builds his philosophical thinking from the philosophical thoughts of the Stoics and Augustines. His philosophy of man carries the idea of liberation for a life that is free from oppression and works only for the glory of God. This philosophy about humans was then passed down in thoughts related to church and state, as well as social human construction during this pandemic.